(untitled) (Research, Society and Development, 2021)
This study analyzes and comments the Administrative Act 502 of the Brazilian National Council for Scientific and Technological Development (CNPq), of May 12, 2021, which institutes Intellectual Property Law rules applicable to the Council’s relations with R,D&I project executors, fellows and researchers benefited by applications, as well as other partners linked to the beneficiaries. The work reveals interfaces between the administrative act and the Brazilian Statutory Intellectual Property rights, as well as the norms related to encouraging innovation and access to information. The study indicates that, although the discipline on the subject is not new within the scope of the CNPq, the administrative act systematically reinforce the importance of the commitment that incentives beneficiaries must assume the management and protection of intellectual property rights, in favor of social and national economic development. It also considers that CAPES (the Brazilian Coordination for the Improvement of Higher Education Personnel) needs to improve the guidelines on the subject, in order to more effectively include the valuation of IP titles as quality indicators of national undergraduate and graduate programs.